578 Sleep Attitudes and Beliefs in Children with Juvenile Idiopathic Arthritis and Their Caregivers. (3rd May 2021) - Zhai, Shumenghui; Ward, Teresa; Palermo, Tonya; Ringold, Sarah
Abstract: Introduction: Sleep deficiency is highly comorbid in children with juvenile idiopathic arthritis (JIA), affecting approximately 40% of children. In this study, we examined children's and parents' beliefs and attitudes about sleep, their self-efficacy, and self-regulation in sleep-related behaviors and managing JIA, and if these factors were associated with their self-report and actigraphic sleep patterns. Methods: The sample included 44 children with JIA (22 girls; mean age 10.5±1.8) and their parents. Dyads completed the Dysfunctional Beliefs and Attitudes about Sleep Scale and Self-Efficacy Scale. Children completed the Index of self-regulation. Parents completed the Pittsburgh Sleep Quality Index and PROMIS sleep-disturbance. Children wore an actiwatch and completed electronic sleep diaries for ten days. Scored actigraphy variables included children's total sleep time (TST), wake time after sleep onset (WASO), sleep efficiency (SE, %); sleep diaries included the variables of children's time in bed (TIB). Parents' self-reported variables included sleep-disturbances and sleep quality (SQ). Results: Children's mean TST was 7.7 hours (±0.7), mean SE of 77%, and mean WASO of 1.1 hours (±0.4). After adjusting for child sex and age, children's beliefs and attitudes towards sleep (BAS) were positively correlated with their self-efficacy in carrying out sleep-related behaviors (r=.6, p<.0001). Parents' BAS were positively correlated with child self-efficacy in sleep (r=.4, p<.05) and TIB (r=.4, p<.001). Children's self-regulation was positively correlated with parents' SQ (r=.4, p<.05). In the first regression model, parents' self-efficacy in managing their child's JIA and parents' sleep disturbances explained 25% of the variance of children's TST, (F(4, 35)=2.8, p=.039). Both parents' self-efficacy and sleep disturbances were significant predictors of children's TST. In the second regression model, children's self-regulation, self-efficacy, and parents' sleep disturbances explained 32% of the variance of parents' self-reported SQ, (F (3, 39)= 6.12, p=.002). Conclusion: The findings suggest that self-efficacy, self-regulation, BAS in both children and parents were associated with better sleep health. Interventions that incorporate parent-child shared decision making about sleep-related knowledge, motivation, skills for setting/achieving goals, and problem-solving strategies are needed for families with children with JIA and sleep deficiency. Support (if any): This work was supported by the NIH/ /NINR (P30NR016585, R21NR01747).